2022
DOI: 10.3390/dj10080154
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation of Swedish Snus, Nicotine Pouches and Other Tobacco Products with Oral Mucosal Health and Salivary Biomarkers

Abstract: In society, tobacco products, such as e-cigarettes, and smokeless tobacco products, such as snus and nicotine pouches, are becoming more attractive. There is still a lack of information regarding the effects of these products on the oral mucosa and oral saliva biomarkers. The aim of this study is to evaluate oral mucosa and the presence of inflammatory biomarkers IL-6, IL-1, IL-8, TNF alpha and LRG-1 in saliva. Respondents were divided in four groups based on their tobacco product usage. Oral examination was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…In three studies, 12 - 14 it was higher in conventional smokers, and in others, 15 - 17 e-cigarette users had higher levels of IL-1β. IL-6 biomarker was assessed in four studies, and all of them except one, 16 reported higher levels in conventional smokers. Also, three studies evaluated IL-8 and 15 - 17 showed higher IL-8 biomarker levels in conventional smokers, and in one study, 16 it was vice versa.…”
Section: Resultsmentioning
confidence: 99%
“…In three studies, 12 - 14 it was higher in conventional smokers, and in others, 15 - 17 e-cigarette users had higher levels of IL-1β. IL-6 biomarker was assessed in four studies, and all of them except one, 16 reported higher levels in conventional smokers. Also, three studies evaluated IL-8 and 15 - 17 showed higher IL-8 biomarker levels in conventional smokers, and in one study, 16 it was vice versa.…”
Section: Resultsmentioning
confidence: 99%
“…Local concentrations might be significantly higher than after ingestion and adverse effects at the site of use are thus most likely. In fact, mucosal changes have been reported in users of snus and nicotine pouches (Miluna et al 2022 ). Shao et al ( 2022 ) analyzed posts related to nicotine pouches on the platform Reddit and found that many users experienced gum problems upon usage of nicotine pouches.…”
Section: Discussionmentioning
confidence: 99%
“…Miluna et al confirmed in their study that there is a statistically significant correlation between how many years tobacco products were used and mucosal changes that could be seen in patients using tobacco products for 5-10 years. [39] It would be essential to educate teenagers at in early age about the negative effects of snus, as the duration of regular usage is crucial in developing irreversible changes.…”
Section: Importance Of Prevention In Periodontitis and Oral Cancermentioning
confidence: 99%